Effect of oral vitamin K prophylaxis on prothrombine time and activated partial thromboplastin time: a randomized controlled comparison with an intramuscular vitamin K in infants - V. Lily Limantara; Sudaryat S.; I. B. Mudita; W. Retayasa; M. Kardana (Indonesian Pediatric Society Publishing House, 2007)
Background Low plasma concentration of vitamin K in the newborn accounts for serious bleeding in the neonatal period and early infancy. The aim of prophylactic vitamin K is to prevent bleeding. Oral prophylaxis is preferable to intramuscular (IM) administration because oral administration is less expensive and less traumatic. Objective To compare oral vs. intramuscular vitamin K on prothrombine time (PT) and activated partial thromboplastin time (APTT) during the first 60 days of life. Methods We randomized newborn infants to either receive oral vitamin K 2 mg at birth and repeated at 7 and 30 days of life or the 1 mg intramuscular vitamin K. PT and APTT were monitored at 0, 15, and 45 days of age. Independent t-test, repeated measurement, and regression analysis were used for statistical analyses and comparison of the results. Results Fifty infants were assigned into the oral group and 50 to the IM group. All participants completed 60 days of study. Both PT and APTT decreased after administration of oral or IM vitamin K, and the values did not differ significantly at any time point and through the period of investigation. Using regression analysis it was shown that only vitamin K administration was correlated with PT and APTT with P value were 0.044 and 0.036, respectively. During 60 days of study, there was no hemorrhagic diathesis in both groups. Conclusions Through the first 60 days of life, 3 doses of oral vitamin K maintain hemostasis by decreasing PT and APTT in infants at values equal to those achieved by the intramuscular preparation. Diathesis hemorrhagic event did not occur in both groups.